A compact three port power divider with tunable power ratio. Issue 2 (21st December 2012) - Sahyoun, Wdalaa; Jrad, Akil; Duchamp, Jean Marc; El‐Helwani, Amer; Ferrari, Philippe
Abstract This article presents a novel method for the design of tunable and miniaturized power dividers.It is based on three impedance transformers and requires a single bias voltage command, instead of three commands needed for more classical designs. This single voltage simplifies the power divider in terms of design and use. For a proof‐of‐concept, a power divider with a 950 MHz working frequency has been designed, with two output varactors tuning the power repartition through the two output ports. Thanks to the developed approach, the miniaturization ratio between our power divider and the Wilkinson one is equal to 75.5% at 950 MHz. Measurements show a wide tunable power ratio between the two output ports (1:3.4), a very good matching in the pass band (return loss better than 16 dB), low insertion loss (0.6 dB), and a tunable bandwidth of ±15%. © 2012 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:357–363, 2012; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27297